Diagnostic accuracy of colposcopy with dynamic spectral imaging for cytology-negative/high-risk HPV positive (failed test of cure) after large loop excision of the transformation zone (LLETZ) of the cervix: Results of the DySIS colposcopy 1 study. Issue 1 (January 2018) - Founta, Christina; Papagiannakis, Emmanouil; Ratnavelu, Nithya; Feusi, Arlene; Natsis, Stavros; Bradbury, Melissa; Fisher, Ann; Naik, Raj
Abstract : Abstract: After treatment for cervical intraepithelial neoplasia (CIN), in the UK women who are cytology-negative, high-risk (HR) human papilloma virus (HPV) positive are referred to colposcopy. This pilot study assessed the incidence of residual/recurrent CIN and the diagnostic accuracy of colposcopy with dynamic spectral imaging (DSI) mapping in their detection. This was a prospective service evaluation carried out in a UK National Health Service (NHS) colposcopy clinic. All women, referred with negative cytology/HR-HPV positive result following treatment for CIN from March 2013 until November 2014, who were examined with the DSI digital colposcope were included. We excluded 3 cases because of poor-quality imaging from user errors. Everyday clinical practice was followed. Initial colposcopic impression, DSI map indication, and biopsy site selections were recorded. CIN2+ was considered the primary outcome and CIN of any grade a secondary outcome. A total of 105 women were included of which 5 (4.8%) had CIN2+ histology and 24 (22.9%) had CIN1. Pre-DSI map colposcopy suggested normal/low grade in all 5 of the CIN2+ cases and DSI suggested high-grade (HG) CIN in 4 of the 5 cases. Sensitivity of standard colposcopy for CIN2+ was 0%, improving to 80% with the incorporation of the DSI map. The CIN burden in this population is higher than previously expected. Colposcopic identification of HG CIN appears to improve significantly with DSI in this cohort leading to refinement in patient management. A larger, multicentric prospective study (DySIS colposcopy 2) is planned to confirm these initial findings.